2012
DOI: 10.1159/000339940
|View full text |Cite
|
Sign up to set email alerts
|

Combined Values of Serum Albumin, C-Reactive Protein and Body Mass Index at Dialysis Initiation Accurately Predicts Long-Term Mortality

Abstract: Background: Protein-energy wasting and chronic inflammation are prevalent in patients with end-stage renal disease (ESRD). We investigated the combination of serum albumin, C-reactive protein (CRP) and body mass index (BMI) at initiation of hemodialysis therapy as a predictor of all-cause and cardiovascular disease (CVD) mortality in Japanese ESRD patients. Methods: A total of 1,228 consecutive Japanese ESRD patients on hemodialysis therapy were enrolled and followed for up to 10 years. Patients were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 53 publications
1
34
0
1
Order By: Relevance
“…16 Thus, the declined BMI, as an established marker of PEW and elevated CRP, could consistently predict poor survival in this population. 17,18 We also have reported that elevated CRP levels were associated with a high restenosis rate and death after coronary drug-eluting stenting or with a high amputation rate and death after endovascular therapy in chronic HD patients. 19,20 By the way, serum creatinine or urea nitrogen levels were comparable among quartiles according to CRP levels in our previous study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…16 Thus, the declined BMI, as an established marker of PEW and elevated CRP, could consistently predict poor survival in this population. 17,18 We also have reported that elevated CRP levels were associated with a high restenosis rate and death after coronary drug-eluting stenting or with a high amputation rate and death after endovascular therapy in chronic HD patients. 19,20 By the way, serum creatinine or urea nitrogen levels were comparable among quartiles according to CRP levels in our previous study.…”
Section: Discussionmentioning
confidence: 96%
“…19,20 By the way, serum creatinine or urea nitrogen levels were comparable among quartiles according to CRP levels in our previous study. 18 Thus, the elevated CRP levels do not seems to reflect kidney dysfunction but rather the state of chronic inflammation. In this regard, preoperative comorbid conditions, such as the PEW state or chronic inflammation, should be more carefully observed in this population than in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with ESRD, several mediators of inflammation share a link with cardiovascular disease [34,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63] (Table 1). Indeed, this is quite dubious for C reactive protein (CRP), either in terms of mere association or from a pathogenic perspective.…”
Section: Mechanisms By Which Inflammation May Increase Cardiovascularmentioning
confidence: 99%
“…Indeed, this is quite dubious for C reactive protein (CRP), either in terms of mere association or from a pathogenic perspective. In fact, while in some trials CRP did not merge as a strong independent cardiovascular risk factor (instead of IL-1, IL-6, TNF-α, albumin, and body mass index) [52,53,55,60], the genetic analysis of polymorphisms leading to a gain of function of gene transcription of CRP failed to demonstrate a dose-dependent effect of this marker [64] and a possible causal role. Other biomarkers (sTWEAK, MIC-1, CD4 + CD28-null T-cells, RANKL, pentraxin3, CCR5, GAL-3, myeloperoxidase, Lp-PLA 2 , and sCD14) , have also been linked to cardiovascular risk in ESRD [32,34,45,46,47,48,51,57,61,62,63].…”
Section: Mechanisms By Which Inflammation May Increase Cardiovascularmentioning
confidence: 99%
“…Inflammatory markers such as C-reactive protein, interleukin 6 and fibrinogen are all positively correlated with cardiovascular death. In flam mation and malnutrition are related (19), and in many studies they were included toget her in cardiovascular risk scores (malnutrition-inflammationathe rosclerosis (MIA) syndrome, prognostic inflammatory and nutritional index (PINI), etc.) (20,21).…”
Section: Introductionmentioning
confidence: 99%